Investigating the Determinants of Non-Performing Loan: Loan Monitoring As a Moderating Variable - Khafid, Muhammad; ., Fachrurrozie; Anisykurlillah, Indah (KnE Social Sciences, 2020)
The objectives of the study are: 1) to analyze the effects of Capital Adequacy Ratio (CAR), Credit Risk, Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) to Non- Performing Loan (NPL); 2) to analyze the role of loan monitoring in moderating the effects of CAR, credit risk, LDR, and NIM on NPL. It was a quantitative study. The subject of the study was the Republic of Indonesia Employee Cooperative (KPRI) which had saving and loan business units. Data were collected by conducting documentation (to collect data on CAR, Credit Risk, LDL, NIM, and NPL) and distributing questionnaires (to collect data on loan monitoring). Then, data were analyzed by moderated regression. The results showed that CAR and NIM did not influence NPL, credit risk and LDR had a positive effect on NPL; Then, loan monitoring moderated the effects of NIM on NPL. However; loan monitoring did not succeed to moderate the effect of CAR, credit risk, and LDR on NPL. Based on the results of the study, the cooperatives engaged in the provision of credit need to consider loan monitoring as a very strategic variable to suppress NPL. Thus; it is suggested for the future research to analyze the effectiveness of loan monitoring system at each loaning institution to suppress NPL. Keywords: Capital Adequacy Ratio, Credit Risk, Loan to Deposit Ratio, Net Income Margin, Non-Performing Loan.